DURABLE GOODS IN URBAN HOUSEHOLDS OF SILVER SINGLES IN POLAND - Zalega, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2023)
Aim: The purpose of this article is to provide some insight into what home infrastructure is present in single seniors’ households. It can be concluded that their home infrastructure is constantly improving, as directly reflected in a better satisfaction of their perceived needs. Methods: The research was conducted in two stages in 2018–2022. In the first of the planned stages, the survey was carried out on a sample of 3,167 silver singles in the period from 1 February to 30 October 2018 and from 1 May to 30 October 2019. The second stage lasted from 1 March to 30 September 2021 and then from 6 February to 30 September 2022 and covered a sample of 3,834 elderly people living alone. In accordance with the research assumptions, the sample included only single people aged 65 and older who took independent consumer decisions on the market. Results: In the analyzed period, the situation of single seniors’ households regarding the possession of almost all durable goods improved, which undoubtedly stems from the fact that these goods are more common and available, e.g., through easily obtainable loans and decreasing product prices. When analyzing home appliances present in silver singles’ households, it can be seen that households tend to replace the existing equipment with new appliances and purchase completely new, previously unknown products. The analysis of the infotainment equipment possessed by silver singles indicates a lower degree of its presence than that of home appliances. Conclusions: In the context of the obtained results, it can be stated that the surveyed households of single elderly people are increasingly better equipped with home appliances, infotainment equipment, and means of transport. This undoubtedly translates into the level at which the needs regarding durable goods are satisfied. The research findings indicate that in both stages, seniors actively attending U3A courses better assess the level of satisfaction of their needs regarding durable goods more frequently than members of parochial clubs.